A conceptual study of connectivity elements towards successful green network / Nor Hamizah Abdul Hamid, Muhamad Ezran Zainal Abdullah and Nik Hanita Nik Mohamad - Nor Hamizah, Abdul Hamid; Muhamad Ezran, Zainal Abdullah; Nik Hanita, Nik Mohamad (2015)
Rapid urbanization has resulted in the loss of natural setting of urban spaces. Fusing the gap between nature andthe city development can generate both common cause and conflict. Green network is a significant shift in linking urban green spaces that will lay out over the coming decades. At present, this green network is not successfully applied due to many open spaces that are not well connected. Hence, connectivity elements provided by the green network plays an important role in helping to conserve urban sustainability. Furthermore, green network is recognized as an effective urban conservation strategy to mitigate the effects of urbanization while maintaining healthy living and sustainability for urban area. However, the opportunity for green network to function as a linkage has not been optimized. Therefore, this research investigates on visitors‟ responses to different dimension of their needs for natural connectivity in the context of sustainable living. Data were collected using interviews and surveys on the scope of connectivity elements towards successful green network. This research offers input on green network by addressing visitors strong preferences towards natural connectivity elements compared to man-made landscape elements.